18F-FDG PET/CT Findings in a Patient With Primary Primitive Neuroectodermal Tumor of the Lung. (15th April 2022) - Chen, Tao; Fan, Jianzhong; Li, Wenfei; Li, Jianqi; Wu, Caiyun
Abstract: Primary primitive neuroectodermal tumor of the lung is an extremely rare and highly malignant neoplasm with a poor prognosis. A 49-year-old man presented with a dry cough and slight pain in the left chest for nearly 1 month. 18 F-FDG PET/CT showed intense 18 F-FDG uptake of the left inferior lung tumor and hypermetabolic mediastinal lymph nodes. Histopathology revealed primitive neuroectodermal tumor after CT-guided transthoracic needle biopsy of the left inferior lung mass was performed.